2002
DOI: 10.1177/08830738020170101501
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β, Tumor Necrosis Factor-α, and Nitrite Levels in Febrile Seizures

Abstract: Proinflammatory cytokines (such as interleukin-1beta, tumor necrosis factor-alpha) and nitric oxide are known to have both direct and indirect modulating effects on neurons and neurotoxic neurotransmitters released during excitation or inflammation. We measured interleukin-1beta, tumor necrosis factor-alpha, and nitrite levels in the peripheral blood and cerebrospinal fluid of children with febrile seizures and compared our results with those of children with febrile illnesses without seizures. Twenty-nine chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 16 publications
3
90
0
3
Order By: Relevance
“…IL-1β and IL-1R1 are up-regulated as a result of seizures in a variety of experimental models, including those induced by electrical stimulation, kainate, bicuculline, and hyperthermia [23,[25][26][27]. Elevated IL-1β and IL-1R1 have also been observed in brain tissue from patients with temporal lobe epilepsy and hippocampal sclerosis, and elevated IL-1β has been reported in cerebrospinal fluid (CSF) from children with febrile seizures [28,29]. In addition to increased IL-1 expression in patients with temporal lobe epilepsy, increases in IL-1β and inflammasome components have also been observed in other seizure disorders such as Rasmussen's encephalitis [30] and malformations of cortical development [31].…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 98%
“…IL-1β and IL-1R1 are up-regulated as a result of seizures in a variety of experimental models, including those induced by electrical stimulation, kainate, bicuculline, and hyperthermia [23,[25][26][27]. Elevated IL-1β and IL-1R1 have also been observed in brain tissue from patients with temporal lobe epilepsy and hippocampal sclerosis, and elevated IL-1β has been reported in cerebrospinal fluid (CSF) from children with febrile seizures [28,29]. In addition to increased IL-1 expression in patients with temporal lobe epilepsy, increases in IL-1β and inflammasome components have also been observed in other seizure disorders such as Rasmussen's encephalitis [30] and malformations of cortical development [31].…”
Section: Il-1β and Hmgb1 Expression In Seizuresmentioning
confidence: 98%
“…Febrile seizures have been shown to be associated with increased IL-1β levels in CNS and blood plasma (68,69), and such IL-1β levels associated with a genetic polymorphism (70,71). IL-1β can act on the interleukin receptors on astrocytes and via the transcription factor NFκB induce a variety of molecules including the chemokines, cytokines and ERM proteins that are up-regulated in the sclerotic hippocampus.…”
Section: An Integrating Hypothesismentioning
confidence: 99%
“…Recent studies suggested that immunological aspects might be responsible for certain types of primary or secondary forms of epilepsy (for review see [13]). The findings of increased levels of cytokines such as interleukin-6 (IL-6) [14], interleukin-1β (IL-1β) [15] and interleukin-1 receptor antagonist (IL-1ra) [16] in cerebrospinal fluid from patients with epilepsy and the aggravating effect of IL-1β, one of the most important pro-inflammatory cytokines, in experimental models of epilepsy [8,9], suggest that the study of inflammatory factors involved in the pathogenesis of epileptic disorders can bring new insights into the molecular mechanisms and etiology of epilepsy.…”
Section: Introductionmentioning
confidence: 99%